2009
DOI: 10.1016/j.bpj.2009.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Assembly and Budding Occur through an Actin-Driven Mechanism

Abstract: The assembly and budding of a new virus is a fundamental step in retroviral replication. Yet, despite substantial progress in the structural and biochemical characterization of retroviral budding, the underlying physical mechanism remains poorly understood, particularly with respect to the mechanism by which the virus overcomes the energy barrier associated with the formation of high membrane curvature during viral budding. Using atomic force, fluorescence, and transmission electron microscopy, we find that bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
95
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(103 citation statements)
references
References 36 publications
7
95
0
Order By: Relevance
“…The observation of dense F-actin networks in the close vicinity of and often pointing toward viral buds in our cET study (21) as well as the AFM results showing asters at HIV-1 budding sites presumed to represent F-actin cables (15) suggested an active involvement of F-actin in HIV-1 assembly and/or release. Moreover, Gladnikoff et al (15) reported that these asters were dependent on the presence of the NC domain in Gag and were not observed for Gag(LZ).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The observation of dense F-actin networks in the close vicinity of and often pointing toward viral buds in our cET study (21) as well as the AFM results showing asters at HIV-1 budding sites presumed to represent F-actin cables (15) suggested an active involvement of F-actin in HIV-1 assembly and/or release. Moreover, Gladnikoff et al (15) reported that these asters were dependent on the presence of the NC domain in Gag and were not observed for Gag(LZ).…”
Section: Discussionsupporting
confidence: 60%
“…Mutational analyses showed that F-actin binding to the NC domain did not require the interaction of this domain with the viral RNA (13,14). A role of the NC domain in F-actin recruitment was supported by an investigation of viral budding sites at the surface of HIV-1 and murine leukemia virus (MLV) Gag-expressing HeLa and NIH 3T3 cells by atomic force microscopy (AFM) (15). That study reported prominent star-shaped structures ("asters") with arm lengths of ϳ0.5 to 2.5 m centered at a subset of budding sites.…”
mentioning
confidence: 99%
“…Is actin dynamics regulated by HIV for promoting budding and virion release? 125 These questions remain to be addressed.…”
mentioning
confidence: 99%
“…[87][88][89] Actin and actin-binding proteins are found inside HIV-1 virions 15,121 raising the question of a potential role of actin cytoskeleton dynamic in either Gag trafficking or in virion budding. 20,[122][123][124][125] The Gag NC domain of several retroviruses (HIV, MLV, EIAV) is known to interact with actin. Indeed, Gag multimerization is required for filamentous actin-Gag association during EIAV assembly.…”
mentioning
confidence: 99%
“…The actin cytoskeleton is known to be involved in several steps of the HIV-1 cycle, including entry (18,20,24), nucleocapsid transport toward the host nucleus (25,26), and viral assembly and budding (11,27,28). Some recent reports suggest that although F-actin polymerization is needed for receptor clustering, it causes a physical restriction for the following nucleocapsid entry (26,29 of the actin-severing protein cofilin has been associated with enhanced HIV entry (26).…”
Section: Hiv-1 Contact With Target Cells Triggers F-actin Rearrangemementioning
confidence: 99%